PENDAMPINGAN REMAJA PEREMPUAN AGAR MENGHINDARI PERNIKAHAN DINI DI JEMAAT GKSI SYALOM UNSE - Septiana Christi Gulo; Dyulius Thomas Bilo (Jurnal PKM Setiadharma, 2022)
Adolescence is the right time for them to pursue education. Education is very important for teenagers because, through education, their potential can grow. However, it is very sad when teenagers who should focus on learning and pursuing their dreams instead fall into early marriage. The biggest factor in the number of early marriages in the GKSI Syalom Unse congregation is the lack of education. This is caused by parents and children who do not understand the urgency of education itself. This PKM aims to provide understanding and awareness to teenagers to avoid early marriage and provide education on the importance of education. Thus, this PKM program has implications for the need to increase the age of marriage to a more mature age, both in terms of mental, educational, and economic aspects. The method used in accommodating the discussion of early marriage is the lecture method. However, in preparing the material using a qualitative approach with descriptive methods. The results of the implementation of this activity went smoothly and were well responded to by the participants. This activity helps teenagers understand the dangers of early marriage and increases their enthusiasm for studying higher knowledge.